Harpagoside attenuates local bone Erosion and systemic osteoporosis in collagen-induced arthritis in mice - Ju-Young Kim; Yoon-Hee Cheon; Sung-Jun Ahn; Sung Chul Kwak; Chong Hyuk Chung; Chang Hoon Lee; Myeung Su Lee (BMC Complementary Medicine and Therapies, 2022)
Abstract Background Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease that causes local bone erosion and systemic osteoporosis. Harpagoside (HAR), an iridoid glycoside, has various pharmacological effects on pain, arthritis, and inflammation. Our previous study suggests that HAR is more deeply involved in the mechanism of bone loss caused by inflammatory stimuli than hormonal changes. Here, we identified the local and systemic bone loss inhibitory effects of HAR on RA and its intracellular mechanisms using a type 2 collagen-induced arthritis (CIA) mouse model. Methods The anti-osteoporosis and anti-arthritic effects of HAR were evaluated on bone marrow macrophage in vitro and CIA in mice in vivo by obtaining clinical scores, measuring hind paw thickness and inflammatory cytokine levels, micro-CT and histopathological assessments, and cell-based assay. Results HAR markedly reduced the clinical score and incidence rate of CIA in both the prevention and therapy groups. Histological analysis demonstrated that HAR locally ameliorated the destruction of bone and cartilage and the formation of pannus. In this process, HAR decreased the expression of inflammatory cytokines, such as tumor necrosis factor-α, interleukin (IL)-6, and IL-1β in the serum of CIA mice. Additionally, HAR downregulated the expression of receptor activator of nuclear factor-κB ligand and upregulated that of osteoprotegerin. HAR suppressed systemic bone loss by inhibiting osteoclast differentiation and osteoclast marker gene expression in a CIA mouse model. Conclusions Taken together, these findings show the beneficial effect of HAR on local symptoms and systemic bone erosion triggered by inflammatory arthritis.